The Paradox of Grammatical Awareness: Interfacing Explicit Knowledge and Grammaring in English Tense Proficiency: A Case of Pre-Service Teachers - Rizki Alawiya; Nur Ilmi Wathoni (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Grammar is an important aspect of learning a language because it conveys the full meaning of sentences and how readers or listeners understand them, whereas mastery of English grammar is currently seen as a dynamic process called grammaring. In this process, learners must possess explicit knowledge of rules. They are also required to stay aware of how to integrate three dimensions of language: form, meaning, and use. Many studies have focused on analyzing students' writing errors. Meanwhile, this study aims to examine students' grammatical awareness when identifying and explaining the use of English tenses in a given context. The research involved first-year students in the English Education Department in the 2025/2026 academic year. A descriptive quantitative method was employed to analyze and describe students' current grammatical proficiency, using data from their written responses to a final examination in the Basic Grammar course. The findings showed that students performed better at identifying tenses (54.17%) rather than at explaining their use (43.33%). A paradoxical trend also emerged: whereas the Simple Present produced strong identification but poor explanation accuracy (70% vs 30%), the Past Continuous showed the opposite pattern (30% vs 56.7%). These findings suggest that students have disjointed explicit knowledge, frequently depending on intuitive recognition or memorization instead of a cohesive comprehension of Form, Meaning, and Use.